Investigating factors responsible for boredom in English classes: The case of advanced learners. (July 2020) - Pawlak, Mirosław; Kruk, Mariusz; Zawodniak, Joanna; Pasikowski, Sławomir
Abstract: Although boredom is among the most commonly experienced emotions in the foreign and second (L2) language classroom, it has so far been given little empirical attention compared to other learner variables, such as anxiety, joy or interest. This paper provides an overview of previous research examining various aspects of boredom in L2 learning and reports the results of a study which aimed to identify factors underlying boredom in the L2 classroom, also looking into the mediating effects of general boredom proneness and attainment. Participants were 107 Polish-speaking English majors who completed the Boredom in Practical English Language Classes Questionnaire (BPELC). The Boredom Proneness Scale and end-of-the-year examination grades were used to divide the participants into less and more prone to boredom as well as high- and low-achievers. Exploratory factor analysis and independent samples t -tests were used to analyze the data. Two factors underlying boredom were extracted: (F1) disengagement, monotony and repetitiveness, and (F2) lack of satisfaction and challenge. Statistically significant differences were revealed between students who were less and more prone to boredom for both factors, and between low- and high-achievers for F1.